Lithium ion electrolyte and lithium ion battery containing same
By using specific compounds and vinyl sulfate compounds as additives in lithium-ion batteries, a stable interface film is formed, which solves the problems of high cost and short cycle life of lithium-ion batteries, and a significant improvement in battery performance and manufacturing cost is achieved. The reduction.
Patent Information
- Application Number
- CN202411507754.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-17
AI Technical Summary
The cost of preparing electrolyte additives of existing lithium-ion batteries is high, and it is greatly affected by fluctuations in lithium ore prices, and the production requirements of fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluctuations in fluc
The first additive and the second additive are specific compounds and vinyl sulfate compounds, respectively, and synergistically act in the lithium-ion battery to form a stable and tough sulfur-containing organic solid lithium salt interface mask to prevent the electrolyte from facing the positive and negative electrodes. Material damage, repairing damaged interfaces, and extending battery cycle life and storage life.
It reduces the manufacturing cost of lithium-ion batteries, significantly improves the battery's cycle life, storage capacity retention rate and high-temperature performance, reduces high-temperature storage gas production, and is simple and low-cost.
Smart Images

Figure BDA0005104502750000031 
Figure BDA0005104502750000042 
Figure BDA0005104502750000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion electrolyte and a lithium ion battery containing the same. Background Art
[0002] In order to cope with global climate change and energy crisis and build a new power system with new energy as the main body, the efficient conversion and storage of renewable energy is the focus of current scientific research.
[0003] Lithium-ion batteries play a very important role in the development of today's era due to their high energy density, high operating voltage, rechargeability and mature commercial development. With the increase in energy density, the advantages of transition metal cathode materials are obvious. However, these materials often have a relatively high operating voltage. Under high voltage, there is a possibility of particle breakage and interface damage during the cycle, thereby oxidizing the electrolyte and causing the cycle life to decay. Therefore, it is necessary to develop electrolyte additives that can stabilize the positive and negative electrode interfaces under high voltage.
[0004] The lithium salt additives in the existing electrolytes mainly include lithium difluorooxalatoborate (LiDFOB), lithium dioxalatophosphate (LiDFOP), lithium tetrafluoro(oxalate) phosphate (LiOTFP) and lithium difluorophosphate (LiPO 2 F 2 ), for example, CN116706241A discloses an electrolyte and a battery, the electrolyte comprising a first lithium salt, a second lithium salt and a first additive, the first lithium salt comprising at least lithium bis(fluorosulfonyl)imide, the second lithium salt being selected from one or two of lithium difluorooxalate borate and lithium difluorobis(oxalate phosphate); the first additive being methylene disulfonate. The electrolyte can improve the oxidation resistance of the battery at high voltage, and improve the cycle performance and high-temperature storage performance of the battery. For another example, CN112736284A discloses a low-impedance, long-cycle non-aqueous electrolyte and a lithium-ion battery based thereon, the low-impedance, long-cycle non-aqueous electrolyte comprising an electrolyte lithium salt, a non-aqueous organic solvent and an additive, the additive comprising lithium difluorooxalate borate and lithium difluorobis(oxalate phosphate); the impurity H in the non-aqueous electrolyte 2 The concentration of O is below 150 ppm; CO 2 The concentration is 10-800ppm; C 2 O 6 2- The concentration is below 500ppm. In the electrolyte, lithium difluorooxalatoborate and lithium difluorobisoxalatophosphate additives cooperate with each other and re-bond with the surrounding electrolyte membrane with similar groups, which can prevent the continued growth of the electrolyte membrane, control the thickness and stability of the electrode surface film, and limit CO 2and the concentration of percarbonate, which helps to reduce the impedance of the electrolyte membrane on the electrode surface and achieve low impedance and long cycle performance. For another example, CN114566712A discloses a high-voltage lithium-ion battery electrolyte containing lithium difluorophosphate, a preparation method thereof, and a lithium-ion battery, the electrolyte comprising a lithium salt, an organic solvent, and an additive, the additive comprising lithium difluorophosphate; in terms of mass fraction, the lithium difluorophosphate accounts for 3.5-6% of the mass fraction of the electrolyte; the lithium salt is lithium hexafluorophosphate. The electrolyte in the present invention contains a high concentration of lithium difluorophosphate, which can significantly improve the cycle characteristics of the battery.
[0005] However, the preparation cost of the above-mentioned lithium salt additives is high and is greatly affected by fluctuations in lithium ore prices. In addition, fluorine chemical production has high production requirements and limited output, which undoubtedly increases the manufacturing cost of lithium-ion batteries.
[0006] Therefore, in order to reduce the cost of lithium-ion battery electrolyte additives and take into account the need to improve battery performance, it is a technical problem that urgently needs to be solved to provide a lithium-ion electrolyte prepared using low-cost additives and improve the electrochemical properties of lithium-ion batteries such as circulation and storage. Summary of the invention
[0007] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a lithium ion electrolyte and a lithium ion battery containing the same.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a lithium ion electrolyte, characterized in that the lithium ion electrolyte comprises a lithium salt, an organic solvent, a first additive and a second additive, wherein the first additive is a compound represented by formula I and / or a compound represented by formula II, and the second additive is a vinyl sulfate compound;
[0010]
[0011]
[0012] Among them, R 1 , R 2 , R 3 , R 4 and R 5 Independently selected from -H, -CH 3 , -OH, -CHO, -CN, -Cl, or -F.
[0013] In the present invention, the compound represented by Formula I, the compound represented by Formula II and the vinyl sulfate compound can react with lithium ions in a lithium ion battery to form the following chemical formulas (1) to (3):
[0014]
[0015] In formula (3), R 1 and R 2 They can be closed and connected to form a five-membered ring or a six-membered ring.
[0016] The present invention adds a first additive and a second additive to the electrolyte, and the two additives can play a synergistic role in the pre-charging formation and subsequent cycle process of the lithium-ion battery to improve the positive and negative electrode interfaces of the battery. The mechanism of action is as follows:
[0017] First, during the initial pre-charge of the lithium-ion battery, under the action of the first additive and the second additive, a stable and tough organic solid lithium salt interface film containing sulfur can be coated. On the one hand, it can prevent the carbonate in the electrolyte from destroying the interface and bulk structure of the positive and negative electrode materials. On the other hand, it can accelerate the exchange of lithium ions between the solid-liquid interface and reduce the interface impedance.
[0018] Second, in the later stage of the lithium-ion battery cycle, the residual first additive and the second additive in the electrolyte continue to repair the damaged sulfur-containing organic solid lithium salt interface film, maintain its protective effect on the positive and negative electrode material structures, and extend the battery's cycle life and storage life.
[0019] Third, since the second additive has a higher HOMO energy level, it will preferentially form a sulfur-containing SEI film at the interface between the positive and negative electrodes; from equations (1) to (3), it can be seen that the film contains similar structures (RSO 3 Li), thereby hindering the further reaction of the sulfonamide group in the first additive and making it free in the electrolyte; when the existing positive and negative solid electrolyte membranes are damaged in the late cycle and storage stages, the exposed positive and negative electrode materials react with the sulfonamide group of the first additive to repair the original protective layer, thereby extending the cycle and storage life of the battery cell.
[0020] Moreover, the production and preparation of the first additive and the second additive in the present invention are simple, low in cost, and high in yield, and can be obtained based on existing production equipment and production processes or simply improved. Moreover, the first additive and the second additive work synergistically to significantly improve the electrochemical performance of the battery, effectively increase the cycle life, improve high temperature performance, improve storage capacity retention and recovery rate, and reduce high temperature storage gas production.
[0021] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0022] Preferably, the compound represented by formula I is selected from at least one of compound 1-1 and compound 1-2;
[0023]
[0024]
[0025] In the present invention, the CAS number of compound 1-1 is: 51299-07-1.
[0026] The compound represented by formula II is compound 2-1;
[0027]
[0028] In the present invention, compound 2-1 is a lithium salt compound of potassium acesulfame, and its preparation method can refer to the preparation method of potassium acesulfame. Potassium acesulfame is a mature industrial product with simple production and sufficient output. By replacing the potassium hydroxide and potassium salt in the preparation process with the corresponding lithium salt, the production of the lithium salt compound of potassium acesulfame can be achieved, that is, compound 2-1 is obtained.
[0029] Preferably, based on the total mass of the electrolyte as 100%, the amount of the first additive added is T 1 It can be 0.1-10%, for example, it can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, etc., preferably 0.2-2%.
[0030] As a preferred technical solution of the lithium ion electrolyte described in the present invention, the second additive includes any one or a combination of at least two of vinyl sulfate, vinyl disulfate (CAS No.: 1431298-10-0), 4-methyl vinyl sulfate (CAS No.: 174953-30-1), 4-trifluoromethyl vinyl sulfate, methyl vinyl sulfate or spirosulfate (CAS No.: 2125664-08-4).
[0031] In the present invention, the structural formula of sulfite methyl vinyl sulfate is The structural formula of spirovinyl sulfate is
[0032] Preferably, based on the total mass of the electrolyte as 100%, the amount of the second additive added is T 2 It is 0.1-5%, for example, it can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., preferably 0.2-2%.
[0033] Preferably, T 1 and T 2 Satisfy: 0.5% ≤ T 1 +T 2 ≤2%, 1:4≤T 1 / T 2 ≤4:1, preferably 1:4≤T 1 / T 2 ≤2:1.
[0034] As a preferred technical solution of the lithium ion electrolyte of the present invention, the lithium salt comprises lithium hexafluorophosphate (LiPF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluorosulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), LiDFOB, LiDFOP or LiOTFP, or a combination of at least two thereof.
[0035] Preferably, based on the total mass of the electrolyte as 100%, the mass percentage of the lithium salt is 10-20%, for example, it can be 10%, 10.5%, 11%, 12%, 12.5%, 13%, 14%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 19% or 20%, etc.
[0036] Preferably, the organic solvent comprises cyclic carbonate, and at least one of chain carbonate and carboxylic acid ester.
[0037] Preferably, the cyclic carbonate comprises any one or a combination of at least two of ethylene carbonate, propylene carbonate and butylene carbonate.
[0038] Preferably, the volume percentage of the cyclic carbonate in the organic solvent is 15-35%, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35% etc.
[0039] Preferably, the linear carbonate comprises any one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate or ethyl propyl carbonate, or a combination of at least two thereof.
[0040] Preferably, the volume percentage of the linear carbonate in the organic solvent is 45-85%, for example, it can be 45%, 47%, 50%, 52%, 55%, 58%, 60%, 65%, 70%, 75%, 80% or 85%, etc.
[0041] Preferably, the carboxylic acid ester comprises any one of methyl formate, ethyl formate, methyl acetate or ethyl acetate, or a combination of at least two thereof.
[0042] Preferably, the volume percentage of the carboxylic acid ester in the organic solvent is 0-60%, for example, it can be 0%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 24%, 26%, 28%, 30%, 35%, 40%, 45%, 50%, 55% or 60%, etc. Wherein, when the value is 0%, it means that the organic solvent of the present invention does not contain carboxylic acid ester.
[0043] Preferably, the lithium ion electrolyte further includes other additives, and the other additives include any one or a combination of at least two of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate or methylene methanedisulfonate.
[0044] The present invention further introduces other additives into the electrolyte, which is more conducive to improving the cycle life, rate performance and storage performance of the battery cell.
[0045] Preferably, based on the total mass of the electrolyte as 100%, the added amount of the other additives is 0.1-5%, for example, it can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc.
[0046] In a second aspect, the present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and the lithium ion electrolyte described in the first aspect.
[0047] In the present invention, the positive electrode sheet includes a positive electrode active material. The present invention does not specifically limit the type of the positive electrode active material, including but not limited to any one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium iron phosphate or lithium manganese iron phosphate, or a combination of at least two of them.
[0048] In the present invention, the negative electrode sheet includes a negative electrode active material. The present invention does not specifically limit the type of the negative electrode active material, including but not limited to any one of natural graphite, artificial graphite, soft carbon, hard carbon, lithium titanate, silicon, silicon carbon or silicon dioxide, or a combination of at least two thereof.
[0049] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] In the electrolyte of the present invention, the production and preparation of the first additive and the second additive are simple, low in cost, and high in yield, and can be obtained based on existing production equipment and production processes or simply improved. Moreover, the present invention utilizes the synergistic effect of the first additive and the second additive in the electrolyte to significantly improve the electrochemical performance of the battery, effectively increase the cycle life, improve high temperature performance, improve storage capacity retention and recovery rate, and reduce high temperature storage gas production. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0053] In the embodiment of the present invention, the substances used as the first additive include compound A, compound B and compound C.
[0054]
[0055] In the embodiments of the present invention, ethylene carbonate is abbreviated as EC, ethyl methyl carbonate is abbreviated as EMC, and diethyl carbonate is abbreviated as DEC.
[0056] Examples 1-13 and Comparative Examples 1-5
[0057] An electrolyte is provided, comprising a lithium salt, an organic solvent, a first additive and a second additive, and the composition of the electrolyte is shown in Table 1. The "content" herein is in mass percentage, based on the total mass of the electrolyte.
[0058] Table 1
[0059]
[0060]
[0061] The lithium ion battery electrolytes of the above-mentioned examples 1-13 and comparative examples 1-5 are used to prepare lithium ion batteries. The lithium ion battery preparation method is as follows:
[0062] (1) Preparation of positive electrode sheet: The positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.1 Mn 0.3 O 2, referred to as NCM613), conductive additive super-P, binder PVDF are dissolved in solvent N-methylpyrrolidone according to a mass ratio of 96:2:2, mixed evenly to form a positive electrode slurry, and the positive electrode slurry is evenly coated on the current collector aluminum foil with a coating amount of 19 mg / cm 2 , then dried at 85°C, cold pressed, trimmed, cut into pieces, and slit, dried at 85°C under vacuum conditions for 4 hours, and the tabs were welded to produce a lithium-ion battery positive electrode that meets the requirements.
[0063] (2) Preparation of negative electrode sheet: The negative electrode active material artificial graphite, conductive additive super-P, thickener CMC, and binder SBR were dissolved in deionized water at a mass ratio of 96:2:1:1, mixed evenly to form a negative electrode slurry, and the negative electrode slurry was evenly coated on the current collector copper foil with a coating amount of 11.5 mg / cm 2 Then, after drying at 85°C, cold pressing, trimming, cutting, and striping, it is dried at 110°C under vacuum conditions for 4 hours, and the tabs are welded to produce a lithium-ion battery negative electrode sheet that meets the requirements.
[0064] (3) Preparation of lithium-ion battery: The positive electrode sheet, negative electrode sheet and separator (PE film) of the above-mentioned lithium-ion battery are laminated to form a battery with a thickness of 8 mm, a width of 60 mm and a length of 130 mm, and then vacuum-baked at 85°C for 10 h, injected with 20 g of electrolyte, sealed, and allowed to stand at 45°C for 24 h; then pre-charged and formed, the pre-charged and formed method is: using a constant current and constant voltage of 0.1C (200mA) to charge to 4.4V, and then discharging at a constant current of 0.1C to 2.8V, repeating one charge and discharge cycle, and charging to 3.8V at 0.1C to obtain the lithium-ion battery.
[0065] The performance of the lithium-ion battery prepared above was tested, and the specific test method is as follows:
[0066] Battery impedance test: At room temperature (25°C), the battery cell is cycled 3 times at 0.33C, and then charged to 4.4V using 0.33C constant current and constant voltage. The last discharge capacity is taken as C 1 , using 0.33C 1 Discharge for 90 minutes to 50% SOC, stand for 15 minutes, and then discharge at 5A constant current for 10 seconds. The battery impedance is the voltage difference divided by the current in this test section.
[0067] Cycle test: In a constant temperature room of 25℃, discharge at a constant current of 1C to 2.8V, let it stand for 10min, then charge at a constant current and constant voltage of 1C to 4.4V, let it stand for 10min, and repeat this cycle for 800 cycles. The ratio of the discharge capacity after 800 cycles to the initial discharge capacity is taken as the 800-cycle capacity retention rate of the battery cell.
[0068] Storage test: At 25°C, discharge at 1C constant current to 2.8V, let stand for 10 minutes, then charge at 1C constant current and constant voltage to 4.4V. Use the drainage method to measure the cell volume V 0 . The battery cell was transferred to a 60℃ oven and stored for 1 month before being taken out. Discharged to 2.8V using 1C constant current, the ratio of this discharge capacity to the initial capacity is the storage capacity retention rate; charged to 4.4V using 1C constant current and constant voltage, the ratio of this charge capacity to the initial capacity is the storage capacity recovery rate; the drainage method was used again to test the battery cell volume V 1 , the storage volume expansion rate is calculated, storage volume expansion rate = (V 1 -V 0 ) / V 0 ×100%.
[0069] The test results are shown in Table 1.
[0070] Table 1
[0071]
[0072]
[0073] As can be seen from Table 1, the present invention can improve the cycle life of the battery, reduce the impedance growth rate during the cycle, and improve the 60°C high-temperature storage capacity retention rate and recovery rate by adding the first additive and the second additive to the electrolyte and utilizing the synergistic effect between the two. Its working principle may be: in the pre-charging stage, the second additive forms a more uniform interface film at the positive and negative electrode interfaces, improves the cycle stability and high-temperature stability of the battery cell, and reduces the gas production of the oxidized electrolyte caused by the rupture of the positive electrode material; in the later stage of cycle storage, the first additive continuously repairs the solid electrolyte membrane and prolongs the cycle life of the battery.
[0074] It can be seen from the data of Examples 1-5 and Comparative Examples 1-5 that the addition of the first additive and the second additive can effectively improve the battery cell cycle, storage, and gas production performance. Moreover, the amount of the first additive added also affects the battery cell performance. The amount added needs to be within a reasonable range to ensure stable film formation. The recommended amount of the first additive added is 0.2-2%; when the amount added is too little, although the battery impedance is low, the electrical performance is not improved enough, and the loss of the interface film during the cycle cannot be effectively repaired; at the same time, when the amount added is too much, the initial film is thicker, which affects the interface impedance and the cycle performance.
[0075] It can be seen from Examples 6-7 that compounds with similar structures to the first additive can also improve the performance of the battery cell.
[0076] It can be seen from Examples 8-9 that the performance of the battery can be regulated and optimized by adding other additives to the electrolyte. The combination of vinylene carbonate, 1,3-propane sultone and tris(trimethylsilyl)borate can improve the electrochemical performance of the battery better than the combination of vinylene carbonate and tris(trimethylsilyl)borate.
[0077] Based on Examples 10-11, the amount of the second additive is adjusted. Increasing the amount of the additive is beneficial to interface protection. However, for more stable and technologically mature positive electrode materials (such as NCM613), an excessively thick interface film will also increase interface impedance and deteriorate the cycle.
[0078] Comparison between Comparative Example 1 and Comparative Examples 3-4 shows that when only one additive is added, the electrochemical performance is slightly improved compared to when no additive is added, but inferior to when the first and second additives are added simultaneously. Comparative Example 2 introduces ethylene carbonate as an additive compared to Comparative Example 1, and although the electrochemical performance of the battery is improved to a certain extent, it is still inferior to the battery containing the first additive and / or the second additive in the electrolyte.
[0079] At the same time, it can be seen from Examples 1-13 that when the first additive is added in an amount T 1 In the range of 0.2-2%, and 0.5% ≤ T 1 +T 2 When the ratio of the amount of the first additive to the amount of the second additive is ≤2%, the electrochemical performance of the battery is better. Example 3 and Example 5 do not meet this relationship, resulting in a decrease in battery performance. By comparing Examples 2-4, it can be seen that the ratio of the amount of the first additive to the amount of the second additive is T 1 / T 2 There is a preferred range. Compared with Example 2, T in Example 3 1 / T 2 If it is too small, the battery performance will be reduced.
[0080] By comparing Example 2 with Example 4, it can be seen that T in Example 4 1 / T 2 =4:1, compared with T in Example 2 1 / T 2 =2:1, due to the high proportion of the first additive, the performance of the battery is worse than that of Example 2.
[0081] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A lithium ion electrolyte, It is characterized in that The lithium ion electrolyte comprises a lithium salt, an organic solvent, a first additive and a second additive, wherein the first additive is a compound represented by formula I and / or a compound represented by formula II, and the second additive is a vinyl sulfate compound; Among them, R 1 , R 2 , R 3 , R 4 and R 5 Independently selected from -H, -CH 3 , -OH, -CHO, -CN, -Cl, or -F.
2. The lithium ion electrolyte according to claim 1, It is characterized in that The compound represented by formula I is at least one selected from compound 1-1 and compound 1-2; The compound represented by formula II is compound 2-1; 3. The lithium ion electrolyte according to claim 1, It is characterized in that Taking the total mass of the electrolyte as 100%, the amount of the first additive added is T 1 It is 0.1-10%, preferably 0.2-2%.
4. The lithium ion electrolyte according to claim 1, It is characterized in that The second additive includes any one of vinyl sulfate, vinyl bissulfate, 4-methyl vinyl sulfate, 4-trifluoromethyl vinyl sulfate, methyl vinyl sulfate or spiro vinyl sulfate, or a combination of at least two thereof.
5. The lithium ion electrolyte according to claim 1, It is characterized in that Based on the total mass of the electrolyte as 100%, the amount of the second additive added is T 2 It is 0.1-5%, preferably 0.2-2%.
6. The lithium ion electrolyte according to claim 1, It is characterized in that T 1 and T 2 Satisfy: 0.5% ≤ T 1 +T 2 ≤2%, 1:4≤T 1 / T 2 ≤4:1, preferably 1:4≤T 1 / T 2 ≤2:
1.
7. The lithium ion electrolyte according to claim 1, It is characterized in that The lithium salt comprises any one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(oxalatophosphate) or lithium tetrafluoro(oxalate)phosphate, or a combination of at least two thereof; Taking the total mass of the electrolyte as 100%, the mass percentage of the lithium salt is 10-20%.
8. The lithium ion electrolyte according to claim 1, It is characterized in that The organic solvent comprises a cyclic carbonate, and at least one of a chain carbonate and a carboxylate; Preferably, the cyclic carbonate comprises any one or a combination of at least two of ethylene carbonate, propylene carbonate and butylene carbonate; preferably, the volume percentage of the cyclic carbonate in the organic solvent is 15-35%; Preferably, the linear carbonate comprises any one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate or ethyl propyl carbonate, or a combination of at least two thereof; Preferably, the volume percentage of the linear carbonate in the organic solvent is 45-85%; Preferably, the carboxylic acid ester comprises any one or a combination of at least two of methyl formate, ethyl formate, methyl acetate or ethyl acetate; Preferably, the volume percentage of the carboxylic acid ester in the organic solvent is 0-60%.
9. The lithium ion electrolyte according to any one of claims 1 to 8, It is characterized in that The lithium ion electrolyte further includes other additives, wherein the other additives include any one of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate or methylene methanedisulfonate or a combination of at least two thereof; Preferably, based on the total mass of the electrolyte being 100%, the amount of the other additives added is 0.1-5%.
10. A lithium ion battery, It is characterized in that The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and the lithium-ion electrolyte according to any one of claims 1 to 9.
Citation Information
Patent Citations
Acesulfame lithium and preparation method thereof, and application in non-aqueous electrolytic solution
CN111333595A
Quick-charge type lithium ion battery and preparation method and application thereof
CN118553914A
Process for the preparation of 6-methyl-3,4-dihydro-1,2,3-oxathiazin-4-one 2,2-dioxide and the purification thereof
CN86105877A
System for automatically rotating a sterring wheel of an agricultural machine
KR102406547B1
Nonaqueous electrolyte solution for secondary battery and nonaqueous electrolyte secondary battery
US20160126592A1
